1996
DOI: 10.1074/jbc.271.32.19283
|View full text |Cite
|
Sign up to set email alerts
|

The Luteinizing Hormone/Chorionic Gonadotropin Receptor Has Distinct Transmembrane Conductors for cAMP and Inositol Phosphate Signals

Abstract: The luteinizing hormone/chorionic gonadotropin receptor is a member of the seven-transmembrane receptor family. It is coupled, presumably via G s and G q , to two signal pathways involving adenylyl cyclase/cAMP and phospholipase C/inositol phosphate (IP). Little is known about the events prior to G-protein coupling: for example, whether these signals are generated from a single or multiple independent origins and mechanisms, when and where they diverge, and how they are transduced. We report novel observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 29 publications
4
25
1
1
Order By: Relevance
“…3). This may be due to differences in coupling effi- ciency or to the fact that different receptor conformations are involved in activating the two pathways (25,26 (27,28). In contrast to our data on the LHR, the Asp 633 3 Tyr TSHR mutant did not appear to possess a more strongly activating phenotype than Asp 633 3 Glu or other TSHR mutations, nor did it cause constitutive activation of the inositol phosphate pathway (28).…”
contrasting
confidence: 56%
“…3). This may be due to differences in coupling effi- ciency or to the fact that different receptor conformations are involved in activating the two pathways (25,26 (27,28). In contrast to our data on the LHR, the Asp 633 3 Tyr TSHR mutant did not appear to possess a more strongly activating phenotype than Asp 633 3 Glu or other TSHR mutations, nor did it cause constitutive activation of the inositol phosphate pathway (28).…”
contrasting
confidence: 56%
“…1 In pregnancy, the decidua is exposed to vast amounts of human chorionic gonadotropin (hCG) secreted by the syncytiotrophoblast, and signaling through the luteinizing hormone/hCG receptor involves cAMP as a second messenger. 44 All of these ligands are candidates for cAMPdependent induction of decidual KAI1 expression, which we demonstrated in vivo in secretory phase endometrium and in the decidua of pregnancy at least up to the second trimester. We also showed that in cultured decidual cells isolated from term placenta, basal KAI1 expression was present and could further be stimulated by cAMP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mutations in the third exoplasmic loop of the luteinizing hormone/choriogonadotropin receptor have been shown to abolish preferentially cAMP induction, being more permissive for the IP signaling (45). Moreover, a mutation in the third transmembrane domain of the ␣ 1 -AR produced a constitutive activation of the IP signaling, without affecting the phospholipase A 2 induction (46).…”
Section: Discussionmentioning
confidence: 99%